2018
DOI: 10.1101/358176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Induction and suppression of NF-kB signalling by a DNA virus ofDrosophila

Abstract: Interactions between the insect immune system and RNA viruses have been best studied in Drosophila, where RNA interference, NF-κB and JAK-STAT pathways underlie antiviral immunity. In response to these immune mechanisms, insect viruses have convergently evolved suppressors of RNA interference that act by diverse mechanisms to permit viral replication. However, interactions between the insect immune system and DNA viruses have received less attention, primarily because few Drosophila-infecting DNA virus isolate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…On the other hand, it should be kept in mind that the interaction between host and virus is a complex process in which the immune response of the host is counteracted by the immune escape mechanisms of the virus. A recent study found that Kallithea virus (DNA virus of D. melanogaster ) gp83 inhibits Toll signaling through the regulation of NF-κB transcription factors ( 25 ). The immunosuppression by Kallithea virus infection is also accompanied by the general down-regulation of AMP gene expression ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it should be kept in mind that the interaction between host and virus is a complex process in which the immune response of the host is counteracted by the immune escape mechanisms of the virus. A recent study found that Kallithea virus (DNA virus of D. melanogaster ) gp83 inhibits Toll signaling through the regulation of NF-κB transcription factors ( 25 ). The immunosuppression by Kallithea virus infection is also accompanied by the general down-regulation of AMP gene expression ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that Kallithea virus (DNA virus of D. melanogaster ) gp83 inhibits Toll signaling through the regulation of NF-κB transcription factors ( 25 ). The immunosuppression by Kallithea virus infection is also accompanied by the general down-regulation of AMP gene expression ( 25 ). Because the action of AMPs may be neutralized by the virus, simple tests cannot decide or exclude whether AMPs have antiviral activity.…”
Section: Introductionmentioning
confidence: 99%
“…Kallithea virus has been isolated for experimental study, and reduces male longevity and female fecundity (Palmer et al 2018). Consistent with its presumed niche as a natural pathogen of Drosophila, Kallithea virus encodes a suppressor of D. melanogaster NF-kappa B immune signalling (Palmer et al 2019). Prior to the work described here, the only other reported natural DNA virus infection of a drosophilid was the discovery (again through metagenomic sequencing) of a small number of RNA reads from Invertebrate iridescent virus 31 (IIV31; Armadillidium vulgare iridescent virus) in D. immigrans and D. obscura (Webster et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2018). Consistent with its presumed niche as a natural pathogen of Drosophila , this virus encodes a suppressor of D. melanogaster NF-kappa B immune signalling (Palmer et al . 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation